Meningkatkan Hasil Belajar Pendidikan Pancasila dan Kewarganegaraan Melalui Media Power Point Pada Siswa Kelas IV Sekolah Dasar - Kamal Hidayat; MS Habiburahman; Endang Purwanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The focus of the research is to advance Pancasila and Citizenship (PKN) learning on the topic of Getting to Know the Environment in grade IV of Elementary School through Power Point media. The research approach uses Classroom Action Research (CAR). This study involved grade IV students in the first semester at Bulakrejo 03 Elementary School, Sukoharjo District, in the 2024/2025 academic year. Data were collected through observation, data collection and testing. The data analysis method uses comparative descriptive, namely differentiating PKN learning outcomes between cycles before using Power Point software and learning outcomes after using Power Point for two cycles. The research results can be explained that the initial value of PKN learning outcomes on the topic of Getting to Know the Environment was an average class score of 67.67 with a classical completion level of 53.33%. In cycle I, the average class score increased to 73.00 with classical completion reaching 73.33%. While in cycle II, the average class score increased to 77.00 with classical completion reaching 90.90%. The results of the study show that the use of Power Point media can improve learning outcomes of Pancasila and Citizenship Education on the topic of Getting to Know the Surrounding Environment for fourth grade students of Bulakrejo 03 Elementary School, Sukoharjo District in the 2024/2025 academic year.